A radiographic study of the association between apical periodontitis and technical quality of intraradicular posts and root canal fillings: A cross-sectional study in Qassim Region, Saudi Arabia - Ra'fat Ibrahim Farah; Abdulrahman Sulaiman Aldakhili; Ayoub Sulaiman Alnasser (Wolters Kluwer Medknow Publications, 2017)
Objectives: This study evaluates the association between the apical periodontitis (AP) and quality of intraradicular posts and the quality of root fillings assessed radiographically in Qassim region, Saudi Arabia. Materials and Methods: Digital periapical radiographs of 327 teeth with post-retained restoration were retrieved randomly from the Qassim University screening clinic's digital archives and evaluated. The quality of the intraradicular post and root filling was evaluated according to the optimum criteria. The presence of AP was assessed based on the periapical index scoring system. The relation between the post technical quality, the quality of root filling, and AP was determined. The data were analyzed using Chi-square test and logistic regression. Results: AP was found in 22% of the investigated teeth. Adequate root fillings were found in 69% of roots, and 14% of these cases were associated with AP. In roots with root filling classified as inadequate, 38% had AP with a statistically significant association between the root filling length and the presence of AP (P < 0.001). The most frequently used posts were prefabricated metallic posts (57%). Teeth restored with cast posts and prefabricated metallic posts exhibited AP with a frequency of 42.3% and 25.4%, respectively, and teeth with nonmetallic posts had significantly fewer cases of AP (12.0%) with a statistically significant association between the post type and the presence of AP (P = 0.016). Conclusion: Both the quality of the root filling and the intraradicular post type were correlated significantly with the presence of AP. The technical quality of root fillings and intraradicular posts was adequate. Nevertheless, the use of threaded posts is still a common practice in this study population.